Softer More Frequent Stools in Infants With Difficult Stooling Fed Hydrolyzed Protein Formula With Added Prebiotics: Randomized Controlled Trial - Fabrizio, Veronica; Harris, Cheryl L.; Walsh, Kelly R.; Wampler, Jennifer L.; Zhuang, Weihong; Wu, Steven S. (Frontiers in Pediatrics, 2022)
Objective To evaluate stool consistency in infants with reported hard or infrequent stools fed hydrolyzed protein formula with added prebiotics designed to promote stool softening. Methods In this multi-center, double-blind, controlled study, eligible infants (28–300 days of age at enrollment) were randomized to: partially hydrolyzed cow’s milk protein formula (PHF, 75% carbohydrate as lactose; 12 mg Mg/100 kcal; n = 49) or routine intact protein cow’s milk-based infant formula (Control, 92% carbohydrate as lactose; 8 mg Mg/100 kcal; n = 51) over a 14-day period. Both formulas had a prebiotic blend (polydextrose and galactooligosaccharides, 4 g/L; 1:1 ratio). Parent-reported stool consistency (hard = 1 through watery = 5) and other daily outcomes were collected by diary. Endpoint stool consistency (mean score over last 3 days of study feeding) was the primary outcome. Adverse events were recorded. Results Baseline stool consistency (Control: 1.4 ± 0.1, PHF: 1.4 ± 0.1) and frequency were similar between groups; the majority had hard (n = 61, 64%) or formed (n = 30, 32%) stools. Stool consistency became softer over Day 1–3 (Control: 2.5 ± 0.1, PHF: 2.6 ± 0.1) and remained similar from Day 4 to 6 through study end (post hoc analysis). For PHF vs Control, endpoint stool consistency was significantly softer (3.4 ± 0.1 vs 3.0 ± 0.1; P = 0.019) and frequency significantly higher (1.5 ± 0.1 vs 1.0 ± 0.1; P = 0.002). Crying, fussing, and appearance of pain during stooling decreased from baseline to study end in both groups. Formula intake, infant fussiness and incidence of adverse events were similar between groups. Conclusion An infant formula designed to promote stool softening was well-tolerated and associated with softer, more frequent stools in infants with reported hard or infrequent stools.